Peningkatan Kemampuan Musikalitas Anak Usia Dini melalui Pelatihan Teknik Vokal Dasar di DeBeat Music Course - Setiawan, Clarissa Jessy; Ardini, Ni Wayan; Wiyati, Wahyu Sri (Institut Seni Indonesia Denpasar, 2025)
Purpose: This study aims to develop teaching materials for vocal instructors in order to improve the musicality of early childhood through basic vocal technique training at Debeat Music Course. Research methods: It uses a qualitative method with a case study approach and data collection techniques in the form of participatory observation. This study involved early childhood who participated in the vocal training program at Debeat Music Course as the main subjects. Results and discussion: With the right and structured teaching standards, children's musical abilities at Debeat Music Course can develop optimally according to their level of development. This can be seen in the increase in their ability to recognize tones, basic vocal techniques, and musical expression. Implication: This study shows the importance of developing teaching materials that are appropriate to the child's developmental stage and the preparation of a systematic curriculum to support optimal musical development in early childhood.